2010
DOI: 10.1186/2047-783x-15-s2-120
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines IL-6 and TNF-α and the development of inflammation in obese subjects

Abstract: BackgroundThe development of obesity and related disorders, e.g., type II diabetes (T2D), hypertension, and metabolic disturbances is strongly related to increased levels in proinflammatory cytokines (IL-1, IL-6, and TNF-α). Both IL-6 and TNF-α are secreted by adipocytes and their concentration correlates with the percentage and distribution of fat tissue in the body. Both cytokines are the main factors responsible for the induction of acute phase proteins production (e.g., CRP) and to inflammatory state.Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
161
2
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(182 citation statements)
references
References 14 publications
12
161
2
7
Order By: Relevance
“…Previous studies showed that the TNF-alpha serum levels are increased in obese individuals. 28 Therefore we hypothesise that this subgroup of patients requires higher dose maintenance therapy of ADA at start to overcome TNF-alpha levels already present.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the TNF-alpha serum levels are increased in obese individuals. 28 Therefore we hypothesise that this subgroup of patients requires higher dose maintenance therapy of ADA at start to overcome TNF-alpha levels already present.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is well-known to increase various pro-inflammatory adipokine concentrations in serum and plasma as well as adipose tissue (34,46), whereas mRNA expression levels showed that adipocytes co-cultivated with breast cancer cells also had significantly higher IL-6, IL-1β, and TNF-α levels (7). It has previously been shown that these elevated circulating cytokines (i.e., IL-6 and IL-8) exerted effects at distant sites (47,48), this favors the progression of breast cancer by upregulating the secretion of pro-inflammatory adipokines as well as exacerbates immune cell infiltration, which in turn promoted cancer progression through cellular proliferation, angiogenesis and the inhibition of apoptosis (38,39,49).…”
Section: Inflammatory Markers: Diet-induced Obesity Induces Systemic mentioning
confidence: 99%
“…IL-1, IL-6, TNFa, C-reactive protein), which promotes a chronic inflammatory state in HS. 4,34 Kromann et al 16 found a significant reduction in disease severity after a substantial weight loss of more than 15% following bariatric surgery.…”
Section: Metabolic Syndromementioning
confidence: 99%